DIABETES GESTASIONAL SEBAGAI PREDIKTOR DINI PENYAKIT KARDIOMETABOLIK JANGKA PANJANG: TINJAUAN LITERATUR - Wisda Widiastuti; Abdullah, Dessy; Aryaldy Zulkarnaini; Arief Rinaldy; Desi Aliefia; Gangga Mahatma (Nusantara Hasana Journal, 2026)
Gestational diabetes mellitus (GDM) has long been regarded as a transient metabolic disorder limited to pregnancy. However, growing scientific evidence indicates that GDM represents an early marker of long-term metabolic vulnerability in women. This literature review aims to synthesize current evidence on the association between GDM and the risk of type 2 diabetes mellitus, cardiovascular disease, and other metabolic disorders after pregnancy, as well as its implications for postpartum care and interdisciplinary collaboration. A literature search was conducted using the PubMed, Scopus, and Web of Science databases, focusing on articles published over the past ten years. The review findings show that women with a history of GDM have a significantly increased risk of developing type 2 diabetes mellitus, as well as a higher risk of cardiovascular disease compared with women without a history of GDM, even among those who do not progress to overt diabetes. The underlying mechanisms include persistent insulin resistance, pancreatic β-cell dysfunction, chronic low-grade inflammation, the role of the placenta, and the potential contribution of the gut microbiota. In conclusion, GDM should be understood as an early predictor of long-term cardiometabolic disease. Structured and collaborative postpartum care involving obstetrics and internal medicine is essential to reduce the future burden of disease.